An experimental investigation on finite wings with leading-edge protuberances - Teo, Marcus Jun Jie (Nanyang Technological University, 2023)
Fluid flow characteristics of wings with leading edge tubercles were experimentally investigated in a water tunnel at a Reynolds number of 13292, falling under the transitional Reynolds regime. This experiment is meant to be continuation of a pre-existing experimental study examining fluid flow characteristics of wings but with differing dimensions. The purpose of this is to overcome the transient nature of the vortices in the previous study which may have hindered the understanding of flow separation behaviour of wings with tubercles. Additionally, analysis of flows over the suction side of the wing will be conducted using Particle Image Velocimetry to determine the nature of flows over a tubercle wing against a baseline wing. Comparisons against past studies will also be conducted. Results have shown an overall similarity between the flow behaviour of the experiment wing and wings of past numerical and experimental studies. Of note is the persisting of attached flow regions over certain areas of the wing which is posited to be due to the imparting of momentum from long separation bubbles over saddle-chords. Additionally, the observation of similar phenomena in vastly different Reynolds number testing regimes for wings with similar tubercle configuration lends credence to the idea of geometry being vital for tubercles to confer their benefits to a wing. Specifically, the ratio of tubercle amplitude to tubercle wavelength.